2021
DOI: 10.3390/ijerph182010941
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status and Health-Related Quality of Life in Patients with Peripheral Artery Disease: A Cross-Sectional Study

Abstract: Peripheral artery disease (PAD) is a progressive atherosclerotic disease that negatively affects individuals’ functional status and health-related quality of life (HRQOL). This study aimed to investigate the HRQOL and associated factors in patients with PAD in Korea. We conducted a cross-sectional study using self-administered questionnaires in a tertiary hospital in Seoul. We measured HRQOL using the EuroQol-5 dimensions-5 levels (EQ-5D-5L) questionnaire and the functional status using a PAD-specific walking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Risk factors for PAD include age, race, smoking, hypertension, diabetes, and hyperlipidemia [ 15 , 16 , 17 ]. PAD is associated with considerable physical and psychosocial disease burden, primarily resulting from impaired functional status and quality of life [ 18 , 19 , 20 , 21 , 22 ] Studies conducted in the U.S. and Hungary have highlighted that functional impairment and pain resulting from lower extremity arterial ischemia leads to reduced quality of life and, consequently, a considerable proportion of PAD patients experience severe symptoms of anxiety and depression. Studies have found that it is mainly impaired the lower extremity functioning that lies at the root of an impaired psycho-emotional state, considerably affecting engagement in social activities and family life [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for PAD include age, race, smoking, hypertension, diabetes, and hyperlipidemia [ 15 , 16 , 17 ]. PAD is associated with considerable physical and psychosocial disease burden, primarily resulting from impaired functional status and quality of life [ 18 , 19 , 20 , 21 , 22 ] Studies conducted in the U.S. and Hungary have highlighted that functional impairment and pain resulting from lower extremity arterial ischemia leads to reduced quality of life and, consequently, a considerable proportion of PAD patients experience severe symptoms of anxiety and depression. Studies have found that it is mainly impaired the lower extremity functioning that lies at the root of an impaired psycho-emotional state, considerably affecting engagement in social activities and family life [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral artery disease (PAD) is a cardiovascular disease, characterized by walking difficulties due to intermittent claudication defined by leg muscle pains, fatigue, or cramping induced by exercise or ambulation, and its prevalence rising with age [ 1 , 2 ]. Notably, declined functional status and PAD-related symptoms are associated with poorer health-related quality of life [ 2 , 3 ]. PAD prognosis can be improved by risk factor modification through revascularization, medication, and exercise therapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chronic diseases such as PAD affect psychological well-being by inducing depression, anxiety, and low quality of life [ 20 , 21 ]. Pain and difficulty in walking distances and climbing stairs in patients with PAD are significantly related to quality of life [ 22 ] and well-being [ 23 ].…”
Section: Introductionmentioning
confidence: 99%